Análisis estadístico sobre del impacto de la pandemia covid-19 sobre las tasas de suicidio en Bogotá D.C. (2024)
Since the beginning of 2020, the COVID-19 pandemic has had significant effects globally, causing important changes in people's daily lives and exerting a notable influence on several aspects of public health (Sanabria-Mazo, Useche-Aldana, Ochoa, Rojas-Gualdrón, & Sanz, 2021). This impact has sparked debate about the possible increase in suicide rates, attributed to the measures implemented by the government to prevent the effects of the pandemic. To carry out the research and achieve the stated objectives, a mixed methodology will be followed that consists of several interconnected steps. First, data will be obtained through SALUDATA, a health statistics collection platform supported by the Ministry of Health. This platform provides suicide rate data since 2012, with a detailed breakdown by geographic region.